PENGARUH KONSENTRASI NaOH DAN DOSIS H₂O₂ TERHADAP DAYA SERAP AIR, DAYA SERAP MINYAK DAN WHITENESS - Putra, Valen Divansyah; Kartika, Rachmah Nanda; Kusumantoro, Herbitus Rudi (Politeknik META Industri Cikarang, 2025)
The excessive use of wood as the primary raw material in the paper industry has led to serious environmental issues, including deforestation and land degradation. As a more sustainable alternative, this study aims to utilize sugarcane bagasse as a raw material for organic paper production by varying the concentrations of sodium hydroxide (NaOH) and hydrogen peroxide (H₂O₂) to evaluate their effects on paper quality. This experimental research employed nine treatment combinations of NaOH (3%, 5%, and 7%) and H₂O₂ (10 ml, 12 ml, and 14 ml), with each combination tested in three replications. The quality parameters analyzed included water absorption, oil absorption, whiteness (CIE), and tensile strength. The results indicated that the combination of 7% NaOH and 12 ml H₂O₂ yielded the most optimal paper quality, with the highest whiteness value of 107.2 CIE, water absorption of 629 g/m², and moderate oil absorption. In contrast, excessive H₂O₂ dosage (14 ml) led to a decline in whiteness due to cellulose degradation. These findings highlight the presence of an optimum point in chemical usage, where higher concentrations do not necessarily result in improved paper properties. This research confirms that sugarcane bagasse can serve as a viable and eco-friendly raw material for producing quality organic paper, thus contributing to the advancement of sustainable paper manufacturing practices.